2004
DOI: 10.1096/fj.04-1652fje
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic regulation of immune cells via D 3 dopamine receptor: a pathway mediated by activated T cells

Abstract: Neuro-immune interactions enable mutual regulation of the nervous and immune systems. To date, evidence exists for manipulations of immune cells by neurotransmitters in the periphery. In this study, we suggest the existence of a pathway by which the brain affects immune cells. The pathway we describe here is mediated by dopamine receptors expressed on activated T cells, termed blasts. Blasts can cross the blood brain barrier regardless of antigen specificity and can therefore encounter neurotransmitters in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(123 citation statements)
references
References 43 publications
5
111
0
7
Order By: Relevance
“…However, most of those studies have shown a number of DA-mediated inhibitory effects using high concentrations (.1 mM) that affect multiple DARs. In contrast, a study addressing the role of selective stimulation of D3R in human T cells have shown that pharmacologic stimulation of D3R in activated CD4 + T cells favors expression of the cell surface activation marker CD25 as well as production of the proinflammatory cytokine IFN-g (33). In agreement with this latter study, our findings in this study show both genetic and pharmacologic evidences indicating that D3R stimulation on CD4 + T cells favors T cell activation and production of the proinflammatory cytokines IFN-g and TNF-a (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…However, most of those studies have shown a number of DA-mediated inhibitory effects using high concentrations (.1 mM) that affect multiple DARs. In contrast, a study addressing the role of selective stimulation of D3R in human T cells have shown that pharmacologic stimulation of D3R in activated CD4 + T cells favors expression of the cell surface activation marker CD25 as well as production of the proinflammatory cytokine IFN-g (33). In agreement with this latter study, our findings in this study show both genetic and pharmacologic evidences indicating that D3R stimulation on CD4 + T cells favors T cell activation and production of the proinflammatory cytokines IFN-g and TNF-a (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…It has also been described that stimulation of D3R in resting T cells favors activation of b 1 integrins and adhesion to fibronectin, two critical events required for cell migration (26,29). Importantly, Ilani et al (33) have suggested that D3R stimulation in human activated CD4 + T cells decrease IL-4 and IL-10 synthesis and potentiates IFN-g production, the hallmark cytokine of Th1 cells. The same authors have shown that pharmacologic D3R stimulation in human T cells potentiate expression of surface activation markers (33).…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 99%
See 3 more Smart Citations